Early diagnosis of infection occurs in burned patients and verification in vitro. (25th March 2018) - Zhang, M.; Yang, L.; Du, G.; Duan, S.; Liu, D.; Gao, X.; Li, D.
Abstract: Objective: To explore the trend of CD64 + neutrophils being present in the peripheral blood of patients with burns and verification in vitro. Method: We isolated and purified CD64 + neutrophils from healthy people, stimulated cells with inactivated Staphylococcus aureus in vitro to make them proliferate and analyzed them with Modfit 2 analysis software. Patients with burns were divided into two groups, depending on whether there was a complicated infection or not, and 35 healthy participants were enrolled as blank group. WBC and CD64 + neutrophil counts were detected and then analyzed the specificity and sensitivity according to the ROC curve. Results: The proliferation index of the CD64 + cells in the experimental wells was significantly higher than that in the control wells ( P < .05). The CD64 + cell counts in the peripheral blood of patients in the infection group were significantly higher than patients without infection, but also higher than the healthy people ( P < .05). The sensitivity and specificity of CD64 + cellular diagnosis for burn infection were 94.2% and 76.8%, respectively, according to the ROC curve, which were significantly better than those of the WBCs. Conclusion: CD64 + cells in the peripheral blood of patients with burns complicated by infection increased significantly, and thus, it can be regarded as an early diagnostic indicator of burns with a concurrent infection.